2017
DOI: 10.1515/folmed-2017-0031
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes Determined by Cluster Analysis in Moderate to Severe Bronchial Asthma

Abstract: Our study is the first in Bulgaria in which cluster analysis is applied to asthmatic patients. We identified four clusters. The variables with greatest force for differentiation in our study were: age of asthma onset, duration of diseases, atopy, smoking, blood eosinophils, nonsteroidal anti-inflammatory drugs hypersensitivity, baseline FEV1/FVC and symptoms severity. Our results support the concept of heterogeneity of bronchial asthma and demonstrate that cluster analysis can be an useful tool for phenotyping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…All baseline parameters in the SPRINT trial clinically relevant for hypertension phenotypes were selected. Cluster analysis by an approach similar to that in a previous report 8 was performed on values centred to a mean value of 0 and a standard deviation (SD) of 1. A two-step clustering algorithm was carried out, in which the first step estimates the optimal number of clusters on the basis of silhouette width and the second step does hierarchical clustering for two to 15 clusters using log-likelihood as a distance measure and Schwarz’s Bayesian criterion for clustering.…”
Section: Methodsmentioning
confidence: 99%
“…All baseline parameters in the SPRINT trial clinically relevant for hypertension phenotypes were selected. Cluster analysis by an approach similar to that in a previous report 8 was performed on values centred to a mean value of 0 and a standard deviation (SD) of 1. A two-step clustering algorithm was carried out, in which the first step estimates the optimal number of clusters on the basis of silhouette width and the second step does hierarchical clustering for two to 15 clusters using log-likelihood as a distance measure and Schwarz’s Bayesian criterion for clustering.…”
Section: Methodsmentioning
confidence: 99%
“…In the field of human medical science, studies using cluster analysis for disease classification and diagnosis have been reported (Li, Yang, Li, Wang, & Guan, 2015; Youroukova et al., 2017). In the field of animal science, cluster analysis was used for the classification of genotypes of bovine populations (Fraga et al., 2016) and the classification of sperm motility of swine (Ibănescu, Leiding, & Bollwein, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Programming and modelling the data with R language are done according to the data characteristics of Chinese medicine medication rules, within which the core herbs were clustered by Hierarchical clustering algorithm. For example, Vania M. Youroukova et al analyzed the phenotype of severe bronchial asthma by using cluster analysis and obtained four clusters that provided reference for clinical treatment [9]. The Apriori algorithm in R language data mining software is used to analyze the association rules of core herbs, which is similar to Mateen Shaikh's applying association rule replacement test to test the relationship between genotype and phenotype, and deduced the genotype of candidate population [10].…”
Section: Methodsmentioning
confidence: 99%